Stratigraphy and paleomagnetism of the lava pile south of Isafjardardjup, NW-Iceland (Dataset) ... - L. Kristjansson; H. Johannesson (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Stratigraphy and paleomagnetism of the lava pile south of Isafjardardjup, NW-Iceland ...